Viral Load Among the Sera of Iraqi Hepatitis C Virus Patients - Al-Haidary, Batool A.; Abdul-Kareem, Safa’a; Azziz, Firyal N.; Al-Aakaishi, Raghad Jawed; Al-Mousawy, Athra’a Z. (Journal of the Faculty of Medicine Baghdad, 2008)
Background:Hepatitis C Virus is the main causative agent of hepatitis among blood transfused patients, in which most chronic cases result in liver carcinoma.Materials & Methods:Enzyme-Linked Immunosorbent Assay for HCV, FNF- and IL-12p40 estimation with Recombinant Immunoblotting Assay (RIBA) as a confirmatory test for HCV, have beenapplied for HCV detection in 80 HCV patients' samples in comparison with 30 samples for apparently healthy control, while viral load has been estimated using Branched-DNA (b-DNA) technique for 32 randomly selected positive cases for HCV. Liver function test has been applied for patients' sera in comparison with control.Results & Conclusions:This study reveals highly specificity & sensitivity of ELISA technique for HCV detection which results in 100% positivity by RIBA methods. Moreover, Viral load estimation shows that (71.9%) of HCV sera samples with viral load >615 IU /ml and only (28.1%) with viral load